INTELLECTUAL CAPITAL TERHADAP CAPITAL GAIN MELALUI CORPORATE PERFORMANCE - Andi Harmoko Arifin (POLITEKNIK LP3I JAKARTA, 2023)
This research aims to find out and analyze the effect of Intellectual capital on capital gains through corporate performance. The characteristics of the sample data include data on the financial statements of 10 companies belonging to the automotive company group with a financial reporting period of 6 years. From this data, indicators are calculated using a ratio formula based on variable measurement indicators with statistical application programs, including SPSS version 21 (Statistical Program for Social Science) and AMOS (Analysis Moment of Structure) version 20, which are packages in the SEM (Structural Equation Model) program. ). The results of this study indicate that intellectual capital, which consists of value added capital employed, value added Human capital , and structural capital value has a positive and significant effect on corporate performance. Intellectual capital consists of value added capital employed, value added Human capital , and structural capital value through corporate performance has a positive and significant effect on capital gains. Intellectual capital consisting of value added capital employed, value added Human capital , and structural capital value has a positive and significant impact on capital gains. It indicates that increasing the intellectual capital budget will immediately increase the company's capital gains. Corporate performance has a positive and significant influence on capital gains. It suggests that the level of corporate performance will be followed by the rise and fall of the company's capital gains.Key words: Intellectual Capital, Capital Gain, Corporate Performance